DEVELOPMENT OF PRODUCTION TECHNOLOGY OF COLD DRAWN WIRE ON 13-FOLD WIRE-DRAWING MILLS OF THE FIRM “KOCH” - A. V. Zinovenko (Литьë и металлургия)
The technology of the cold-drawn wire production at 13-fold wire-drawing mills of the firm ''Koch developed.